Estudo eletroquímico de eletrodos extensos e estruturados com nanotubos de carbono - Raphael Longuinhos Monteiro Lobato (2011)
In this work we studied the influence of nanostructures in electrodes of a electrochemical cell using the Cyclic Voltammetry technic. The material used as structured electrode is composed by multiwall carbon nanotubes directly grown on a carbon cloth. In order to study effects introduced by metallic particles on electron transfer properties, some samples were decorated with platinum. We made use of two kinds of electrolytes with different electrochemical properties. The observed electrical current is then described using two models of electrical circuits composed by capacitors and resistors associated in different configurations. This analysis allowed a phenomenological description of the dependence of the double layer capacitance with the rates of variation of the electrical potential difference, in the case of a cell filled with the electrolyte with the species K+ and Cl The results allowed one to conclude that this kind of structured electrodes show greater specifics capacitances. Besides, our analysis using 3, 4 Fe(CN)6 electrolytes showed that our structured electrodes increased the rate of electron transfer processes. Non trivial details of the dynamics of formation of the electrical double layer capacitance in extended electrodes are also reported.